Anatomy and shell shape variability in a land snail Bostryx torallyi (Stylommatophora: Bulimulidae) - Miranda, María José (Revista de Biología Tropical, 2020)
Introduction: The gastropod Bostryx torallyi shows high variability in shell shape and coloration. Subspecies of this organism have been described based on shell characters but, since they were slightly different, they were synonymized afterwards. Until now, shell variability has been analyzed only descriptively and its anatomy is still unknown. Objective: In this study, I provide anatomical information of B. torallyi and apply a geometric morphometric analysis to evaluate the shell shape variation among specimens. Methods: To accomplish this, type material and numerous lots were examined and dissected out. Additionally, relative warp analysis, based on 9 landmarks in ventral view of the shell, was performed using 80 specimens of 9 localities from Bolivia and Argentina. Results: According to our results, geometric morphometrics is a suitable method to evaluate differences in shell shape among localities; for instance, distinctions in the shell were noticeable between gastropods of low and high altitudes. On the other hand, it was established that the coloration of this species is independent of large-scale factors since the examined specimens came from environments with similar conditions. Furthermore, the sculpture of the protoconch and anatomy of B. torallyi coincided with the other Argentinian species of the genus. Conclusions: Therefore, I concluded that a geometric morphometric analysis of shell shape is a good complement to traditional qualitative description of the characteristics of the shell in this species.